2002
DOI: 10.1164/rccm.2105124
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Cardiovascular Disease in Middle-aged Men with Obstructive Sleep Apnea

Abstract: The incidence of a cardiovascular disease (CVD) was explored in a consecutive sleep clinic cohort of 182 middle-aged men (mean age, 46.8 +/- 9.3; range, 30-69 years in 1991) with or without obstructive sleep apnea (OSA). All subjects were free of hypertension or other CVD, pulmonary disease, diabetes mellitus, psychiatric disorder, alcohol dependency, as well as malignancy at baseline. Data were collected via the Swedish Hospital Discharge Register covering a 7-year period before December 31, 1998, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
436
1
28

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 725 publications
(478 citation statements)
references
References 31 publications
(28 reference statements)
7
436
1
28
Order By: Relevance
“…1 Sleep apnoea, or more specifi cally obstructive sleep apnoea (OSA), is a more serious problem as the apnoeic episodes lead to reduced blood oxygen saturation and cardiovascular problems (particularly hypertension) in the long term. 2 OSA also causes signifi cant daytime sleepiness, with impaired daytime functioning and increased risk of road traffi c accidents. [3][4][5][6] Uncomplicated snoring occurs in approximately 40% of the adult population in the UK and approximately 10% of these snorers have OSA.…”
Section: Introductionmentioning
confidence: 99%
“…1 Sleep apnoea, or more specifi cally obstructive sleep apnoea (OSA), is a more serious problem as the apnoeic episodes lead to reduced blood oxygen saturation and cardiovascular problems (particularly hypertension) in the long term. 2 OSA also causes signifi cant daytime sleepiness, with impaired daytime functioning and increased risk of road traffi c accidents. [3][4][5][6] Uncomplicated snoring occurs in approximately 40% of the adult population in the UK and approximately 10% of these snorers have OSA.…”
Section: Introductionmentioning
confidence: 99%
“…OSA is associated with daytime sleepiness, poor academic performance, stroke, hypertension and ischemic heart disease (3,4).Furthermore, not only habitual snoring combined with OSA or upper airway resistance syndrome, but also habitual snoring alone appears to be linked with impaired daytime functioning in adults (5,6). Population based cohort studies revealed age, obesity, smoking, nasal (eg, septal deviation, rhinitis) and pharyngeal (eg, hypertrophy of tonsils, otitis) problems as independent risk factors for self reported habitual snoring (7,8).Professional wrestlers have some of risk factors for snoring including male gender, high body mass index (BMI) and large neck circumference.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even just the coexistence of OSA and T2D has important clinical, public health, and economic implications. They are both independently linked to high cardiovascular morbidity and mortality (6)(7)(8), and both are potential therapeutic targets for either primary or secondary prevention of cardiovascular disease. OSA is also linked to drug-resistant hypertension (9).…”
mentioning
confidence: 99%